Determining highway slope ratio using a method based on slope angle calculation - Yilmaz, Osman Salih; Ozkan, Gulgun; Gulgen, Fatih (SELCUK UNIV PRESS, 2021)
Geographic Information System (GIS) is a vital tool used in numerous areas related to natural science and engineering studies. Managing complex data and obtaining accurate results from the analysis are essential functions of GIS. It is also efficiently used in highway designing both in project and application phases. This study proposes a new calculation method of slope angles to determine the suitable slope modal of a road by using topographic and geological datasets in a GIS environment. Using this method in the preparation phase of the project enables a more accurate calculation of earthwork volume. The proposed method was applied to a highway to prove this idea. The selected road is a significant tertiary of which project was completed by the Turkish General Directorate of Highways. In this study, the calculated values of the project were considered as references. Comparing both results obtained from the proposed method and application project, the accuracy of the slope modal of the proposed method is 71%, and the accuracy of its earthwork volume is 99%. The proposed approach will enable project managers and designers to determine more reliable earthwork volume during project feasibility studies without any application in the field.
Keywords: Geographic information systems (GIS); Highway construction; Stability analysis; Slope ratio; Slope angle; GEOGRAPHIC INFORMATION-SYSTEM; GENETIC ALGORITHMS; OPTIMIZATION; COST; GIS; MODEL; Engineering